Neungjamnong Fertilizer - Neungjamnong, Natthaphat (2016)
Neungjamnomg Company is a poultry farming company that produces a large amount of chicks and chickens. Chicken manure is one of our by-products which is disregarded and sell cheaply (five baht per six kilograms) to middlemen who sell it to fertilizer factories. The factory sells their fertilizers three to seven baht per kilogram. To increase our profitability and generate the effective fertilizer to farmers for developing Thailand’s agriculture, we have planned to establish Neugjamnong Fertilizer under Neungjamnong Company to produce and sell fertilizers that are derived from our by-products. The amount of additional funding, that we need to invest in our capital assets, run business and generate net profits of 4.1 million baht in the second year, is three million baht. This business plan is created to plan our business strategic, operating, marketing and a financial scheme based on the realistic market.